Brand Preference Studies: Scientific Mapping, Research Patterns, and Future Insights - Tanghana, Kelvin Krisdamaiyanto; Apriyanti, Leny (Journal of International Conference Proceedings, 2025)
This study aims to conduct a bibliometric analysis of brand preference research to map its intellectual structure, key contributors, and thematic evolution. Using 696 documents retrieved from the Scopus database covering the period 2015–2024, co-occurrence and citation analyses were employed to identify dominant themes and influential research patterns. The findings reveal that while publication volume has steadily increased, citation accumulation for newer studies remains gradual. Conceptual mapping identifies four major research clusters: Brand Loyalty, Consumer Branding, Youth Marketing, and Brand Strategy. Among these, Consumer Branding emerges as the most dynamic and impactful cluster, characterized by high citation rates and contemporary relevance, while Brand Loyalty and Youth Marketing show thematic stagnation. The United States leads research productivity and impact, followed by growing contributions from India and China. The results suggest that brand preference research is shifting toward consumer-centered and technology-driven models. Future studies should adopt interdisciplinary approaches, integrating sustainability, corporate social responsibility (CSR), and digital transformation to maintain academic relevance and address evolving market dynamics.